Pengetahuan Masyarakat Tentang Penyimpanan Dan Pembuangan Obat Di Ngrayun, Ponorogo - Vidya Kartikaningrum; Riyan Agustin Arinar; Diah Nurcahyani (An-Najat, 2024)
Drug storage is an activity carried out to maintain the quality of drugs.Improper storage of drugs can result in the quality of the drugs being damaged. In addition, improper disposal of drugs has the potential for drug abuse and environmental pollution. The purpose of this study was conducted to determine the level of community knowledge in the storage and disposal of drugs at home in RW 05 Ngrayun Village, Ponorogo Regency. This study used descriptive observational method with a cross sectional approach. The sample in this study was the community of RW 05 Ngrayun Village, Ponorogo Regency with a sample size of 110 respondents. Sampling using purposive sampling technique. The instrument used for this study was a questionnaire with 23 questions consisting of 15 questions about storage and 8 questions about disposal. The results of knowledge about storage of good criteria as much as 3%, enough 8% and less 89%. As for knowledge about disposal with good criteria as much as 5%, enough 35% and less 60%.